Effect of Biosurfactants and non-catalytic proteins on the enzymatic hydrolysis of cellulignin - Mera, Alain Eduard Monsalve (2025)
The enzymatic hydrolysis of lignocellulosic biomass is often hindered by lignin, which acts as a physical barrier and promotes non-productive enzyme adsorption. This study evaluated the potential of soybean protein in powdered and cavitated forms, along with lactonic sophorolipid biosurfactant (LSLB), to enhance sugar yields from cellulignin derived from sugarcane bagasse, a residue with a high lignin content. A BoxBehnken design was used to investigate the effects of enzyme loading (1020 FPU/g cellulignin), soybean protein powder (1030% w/w of dried cellulignin), and LSLB concentration (25250 mg/L) on glucose and xylose yields. Hydrodynamic cavitation was employed to produce soluble soybean protein, achieving a solubility yield of 44.4% w/w in 10 min. The cavitated protein was compared with powdered protein to assess its impact on enzymatic hydrolysis efficiency. The results showed that hydrodynamic cavitation reduced the required SBP dosage while maintaining sugar yields, allowing 10% w/w of dried cellulignin cavitated SBP to achieve glucose and xylose yields comparable to 25% w/w of dried cellulignin noncavitated SBP. Specifically, glucose yield increased by 24.92% (from 34.1% ± 1.01 to 42.6% ± 1.4), and xylose yield by 30.86% (from 32.4% ± 0.53 to 42.4% ± 2.21) compared to the no-additive condition. These improvements were linked to enhanced solubility, increased surface area, and reduced particle size in the cavitated protein. This study highlights hydrodynamic cavitation as a novel approach for modifying soybean protein structure to optimize enzymatic hydrolysis in lignocellulosic bioconversion.